Benefits and harms of copyright restrictions and conditions on burnout and other psychometric assessment scales - Robert G. Badgett; Sudha Xirasagar; Hayrettin Okut (PLoS ONE, 2026)
Introduction Copyright conditions can hinder the scientific and usage impact of essential assessment tools in healthcare, organizational psychology, and other fields. The stories of the Maslach Burnout Inventory (MBI) and the Mini-Mental Status Examination (MMSE) are well-documented. Despite decades-old recommendations to blend copyright restrictions of intellectual property when used for commercial purposes with permissive but distinct copyright terms for non-commercial and scholarly use, few authors of assessment tools do so. Objective To assess whether restrictive copyrights limit the long-term scientific impact of copyright holders (often medical schools/faculty), by inhibiting downstream use, research, and improvement of measurement tools by other researchers. Methods We compared MEDLINE citation trends of two restrictive surveys (requiring royalty payments, prohibiting item modifications) – the Maslach Burnout Inventory (MBI) and the Mini-Mental Status Examination (MMSE) – against four free-to-use and adapt surveys. Our outcome was the annual, theme-relevant citation ratio of each survey since publication. The ratio was the number of publications featuring the scale name in the title or abstract divided by total publications addressing the original theme (purpose) of the scale. We performed paired comparisons of the most recent slopes of the annual citation ratio, pairing each restrictive scale with a permissive scale, totaling eight comparisons. Results The restrictive MBI and MMSE initially showed rising slopes of annual citation ratios, and a decline in later years with negative slopes. Further, the final slope segments for all four permissive surveys were positive, vs. negative for the restrictive surveys, the slope difference being statistically significant for six out of eight comparisons. Conclusions Restrictive copyright conditions on assessment scales risk undermining their long-term scientific and functional relevance. Previously recommended blended copyright approaches can facilitate survey creators’ revenues via commercial use royalties, while sustaining continued scholarly development and noncommercial usage to improve long-term relevance.